Building-related illness (BRI) in all family members caused by mold infestation after dampness damage of the building - Kramer, Axel; Wichelhaus, Thomas A.; Kempf, Volkhard; Hogardt, Michael; Zacharowski, Kai (German Medical Science GMS Publishing House, 2021)
Introduction: In 2010, dampness damage in a single-family house caused a massive mold infestation. In the further course, the 5 family members developed severe health problems. This report investigates the extent and cause of the water damage. In addition, the various visible fungal infestations were analyzed in a specialized laboratory.Results: Due to building construction errors, starting from the basement, an increased moisture penetration of the residential building was detected.Within 2 years, massive mold infestation occurred. In 2016, the following species were detected: andand. Additionally, different black molds were macroscopically detected.The severity of the disease process varied, probably due to the different daily exposure of the family members, and possibly influenced by age. The children presented acute episodes with nocturnal cough, associated with sleep disturbances and respiratory infections with severe rhinitis. In addition, general fatigue was noticeable. The course of the disease was complicated by recurrent nightly nosebleeds. The mother developed a much more severe course as chronic fatigue syndrome. Additionally, the following continuous complaints occurred: sore throat and headache, nocturnal irritable cough, chronic rhinitis, difficulty concentrating, increasing forgetfulness and word-finding disorders, cognitive impairment with reduced short-term memory, extremely dry eyes with red sclerae, morning stiffness, dyspnea, disturbed temperature regulation (chills), increased feeling of thirst, and menstrual disorders. The father's building-related illness (BRI) was comparatively mild due to much lower exposure, with nocturnal irritable cough, rhinitis, and marked fatigue. In 2018, after moving out of the house, the father was symptom-free after 2 weeks, the three children after 6 months, but the mother only after 18 months.Discussion: The symptoms are consistent with reports from the literature, according to which fatigue, sleep disturbances, lack of concentration and headache as well as recurrent infections of the upper respiratory tract are caused by microbial volatile organic compounds (MVOCs) released by molds. The association with recurrent nosebleeds in childhood has not been described in this form before. Conclusion: Since in all family members complete remission of symptoms occurred after cessation of the 6-year exposure, there is no doubt that the BRI was caused by the massive mold infestation.